Role of argyrophilic nucleolar organizer region staining in identification of malignant cells in effusion - Meenu Gill; Uma Singh; Qury S Mahapatra; Sapna Gehlot; Veena Gupta; Rajeev Sen (Journal of Cytology, 2011)
Background: Cytological examination of effusions helps to differentiate between benign and malignant effusions, but fails a definitive diagnosis in a number of cases. The main problem here is to distinguish reactive mesothelial cells from neoplastic cells. Aim: In the present study, we used argyrophilic nucleolar organizer region (AgNOR) staining for diagnosis of benign and malignant effusions. Materials and Methods : In this study, 100 cases of effusion samples were taken and centrifuged. Four smears were prepared from sediment, one each for Leishman, hematoxylin and eosin (H and E) staining and two for AgNOR staining. AgNORs were counted as black dots in the nuclei of all abnormal cells using x100 oil immersion objective. Their dispersion and shape was compared in benign, malignant and atypical cases. Results: Out of 50 pleural effusion samples, 29 were benign, 10 were malignant and 11 atypical. Among the 47 peritoneal effusion samples, 27 were benign, 16 were malignant and 4 atypical. Out of three cases of pericardial effusion samples, one was benign and two were malignant. All effusions were subjected to AgNOR staining. The benign group consisted of cells showing 1 to 2 dots of regular size and shape. In malignant group, 3 to 5 dots of variable size, shape and irregular contours were observed per cell. In atypical group, the reactive mesothelial cells showed 1 to 2 dots, malignant cells showed 3 to 4 irregular dots. Thus, a differentiation was noted between activated mesothelial cells and malignant cells, which was not possible in Leishman and H and E-stained smears alone. Conclusion : Therefore, AgNOR can be branded as an extremely useful additional diagnostic tool for cytodiagnosis of effusions.